Crossmodal Congruency Between Background Music and the Online Store Environment: The Moderating Role of Shopping Goals - Doucé, Lieve; Adams, Carmen; Petit, Olivia; Nijholt, Anton (Frontiers in Psychology, 2022)
Despite the robust evidence that congruent background music in the physical store environment positively affects consumer reactions, less is known about its effects in an online context. The present study aims (1) to examine whether congruency via multiple elicited crossmodal correspondences between background music and the online store environment (e.g., perceived lightness, loudness, and coldness of the cue/environment) leads to more positive affective, evaluative, and behavioral consumer reactions and (2) to investigate the moderating role of shopping goals on this crossmodal congruency effect. Previous research showed that low task-relevant atmospheric cues like music can have a negative effect on consumers when they visit a website with a purchase goal in mind. An online experiment was conducted with 239 respondents randomly assigned to a shopping goal (experiential browsing vs. goal-directed searching) and a music condition (no music, crossmodally congruent music, or crossmodally incongruent music). Our results show that crossmodally incongruent background music (vs. no music) leads to more positive consumer reactions for experiential browsers and more negative consumer reactions for goal-directed searchers. Conversely, crossmodally congruent background music (vs. no music) has a positive effect on experiential browsers and no adverse effect on goal-directed searchers. Additionally, the presence of crossmodally congruent background music leads to more positive consumer reactions than the presence of crossmodally incongruent background music, independent of the shopping goal. We extend previous research on multisensory congruency effects by showing the added value of establishing congruency between music and the store environment via multiple elicited crossmodal correspondences in the online environment, countering previously found negative effects of low-task relevant atmospheric cues for goal-directed searchers.